Republic of Congo : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper on the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) for the Republic of Congo explains medium-to-long-term strategy for poverty reduction. Emerging from a conflict situation, and starting from a low base, Congo has made significant progress in implementing macroeconomic, financial, and structural reforms. Debt relief under the enhanced HIPC Initiative is expected to reduce Congo's external debt by about one-third. The authorities have emphasized that Congo's external debt remains unsustainably high and could further delay its economic and social reform programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet